Hubungan Pendapatan Keluarga dan Ketahanan Pangan dengan Status Gizi Balita pada Era Pandemi Covid-19 di Kabupaten Pasuruan - Nur Indah Dwi Hidayati (Universitas Airlangga, 2023)
Background: The Covid-19 pandemic has resulted in the emergence of nutritional issues among one vulnerable group, which is toddlers, due to inadequate daily nutrient intake. The Covid-19 pandemic has had an impact on various sectors and disrupted activities, such as the ineffectiveness of health services for toddlers during the Covid-19 pandemic and a decline in income so that households find it difficult to share food expenditure with other needs. Objectives: This research explores the connection between family income and food security and the nutritional status of children under five years in Pasuruan Regency during the Covid-19 pandemic. Methods: The research method used is analytical observational with a cross-sectional study design. The sample size consisted of 100 toddlers, selected through multistage sampling, which involves dividing the population into smaller clusters. The research and data collection were conducted from June 2022 to August 2022 at the Pandaan Subdistrict's Integrated Health Center (Posyandu). The US-HFSSM questionnaire was used to assess household food security, while the Weight-for-Age (W/A), Height-for-Age (H/A), and Weight-for-Height (W/H) indices were used to assess the nutritional status of the toddlers. The statistical test employed was the chi-square test. Results: Families with income below UMK are 58%, and 42% of households are in a food insecure situation. An assessment of the nutritional status of children under five years revealed that most of the children under five years fell into the normal weight category (68%), normal height category (79%) and good nutrition category (52%). The results of statistical tests revealed a connection between family income and the nutritional status of infants with the weight-age and weight-height conditions (p=0.016) and (p=0.015), as well as between household food security variable and nutritional status of toddlers in terms of weight-for-age (p=0.040), height-for-age (p=0.013), and weight-for-height (p=0.042). Conclusions: Approximately 58% of families are classified as having income below the minimum wage (UMK). The majority of respondents, 71%, experienced a decrease in family income. About 58% of households were categorized as having vulnerable food security scores, indicating a risk of food insecurity. The assessment of nutritional status among toddlers showed that the majority of them fall into the normal weight category (68%), normal height category (79%), and good nutritional status category (52%)